2020
DOI: 10.1111/trf.15937
|View full text |Cite
|
Sign up to set email alerts
|

The use of cryopreserved platelets in a trauma‐induced hemorrhage model

Abstract: Background Cryopreserved platelet products can be stored for years and are mainly used in military settings. Following thawing, cryopreserved platelets are activated, resulting in faster clot formation but reduced aggregation in vitro, rendering their efficacy in bleeding unknown. Also, concerns remain on the safety of these products. The aim was to investigate the efficacy and safety of cryopreserved platelets in a rat model of traumatic hemorrhage. Study Design and Methods After 1 hour of shock, rats (n = 13… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 37 publications
1
18
0
Order By: Relevance
“…An animal study including rats with traumatic haemorrhage who were subsequently transfused with DTC showed reduced blood component use compared to RSP to reach and maintain a mean arterial pressure of 60 mmHg [ 11 , 12 ]. In thrombocytopenic patients, the use of cryopreserved platelets appears to be safe and effective, and also in trauma [ 12 ], cardiopulmonary surgery [ 9 ] or thrombocytopenia [ 10 , 14 ], the outcome of treatment with frozen platelets was similar to room-stored platelet transfusion. Despite this fact, high-quality evidence from randomized clinical trials for the efficacy of DTC in acute bleeding is still lacking.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…An animal study including rats with traumatic haemorrhage who were subsequently transfused with DTC showed reduced blood component use compared to RSP to reach and maintain a mean arterial pressure of 60 mmHg [ 11 , 12 ]. In thrombocytopenic patients, the use of cryopreserved platelets appears to be safe and effective, and also in trauma [ 12 ], cardiopulmonary surgery [ 9 ] or thrombocytopenia [ 10 , 14 ], the outcome of treatment with frozen platelets was similar to room-stored platelet transfusion. Despite this fact, high-quality evidence from randomized clinical trials for the efficacy of DTC in acute bleeding is still lacking.…”
Section: Discussionmentioning
confidence: 99%
“…Retrospective data from missions from the NLAF show that increased DTC and plasma use as a result of the implementation of an MTP resulted in a significant improvement in chances of survival during armed conflict [ 7 ]. However, in this setting, no RSP were available to provide evidence of an improved haemostatic potential of DTC in the treatment of acute bleeding, as has been suggested by the above-mentioned rat study [ 12 ] and one cardiopulmonary bypass surgery study [ 9 ]. We believe that DTCs provide a suitable and potentially better alternative to RSP in the treatment of bleeding patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The clearance occurs through triggered surface up-regulation of neuraminidases, which perform the vWF-receptor complex’s desialylation, specifically, the GPIbα subunit leading to GPIbα-clustering and rapid platelet clearance by liver phagocytes [ 154 , 187 , 188 ]. Although cryopreservation slows down the metabolism, reduces the risk of bacterial contamination, and is therefore proposed as a prominent alternative to the current storage standard at 22 °C, its application is still under debate since the freeze-thawing-induced activation of platelets may promote the risk of thromboembolic events [ 189 ]. Wang et al compared the proteomic signature of platelets stored at 22 °C, 10 °C, and −80 °C and concluded that different conditions caused different PSLs.…”
Section: Platelets Proteomics In Transfusion Medicinementioning
confidence: 99%
“…(8-10) These differences are likely due to platelet activation and release of platelet derived micro particles after thaw. (11) The use of DTCs in several clinical studies has not led to effectivity or safety issues in trauma (12), thrombocytopenic (11,13) or cardiopulmonary bypass (9) patients and in in rats. (12) In the current introduced multi-centre, single blinded, randomized controlled non-inferiority trial, the objective is to compare the haemostatic effects of DTCs with the currently predominantly used RSPs in the treatment of surgical bleeding and to show that DTCs have at least similar haemostatic effects as compared to RSP.…”
mentioning
confidence: 99%